ON SEVEN OVERLOOKED CURCULIONOIDEA FROM NORTHERN ITALY (Coleoptera) - Caldara, Roberto; Colonnelli, Enzo (Fragmenta entomologica, 2012)
Seven Curculionoidea described from Lombardy (northern Italy) by Virginio Betta in 1857 and overlooked by subsequent authors are here treated. Since the Betta collection where their types are supposed to have been preserved was never traced, neotypes of all of them are designated with the purpose of clarifying their taxonomic status. Revised combinations are: Pseudeuparius pictus (Betta, 1857) comb. rev. from Tropideres Schoenherr, 1823; Pachytychius aericollis (Betta, 1857) comb. rev. from Smicronyx Schoenherr, 1843; Mecinus vittatus (Betta, 1857) comb. rev. from Gymnetron Schoenherr, 1825; Mecinus areolatus (Betta, 1857) comb. rev. from Gymnetron Schoenherr; Mecinus flavipes (Betta, 1857) comb. rev. from Gymnetron Schoenherr. The following new synonymies are established: Pseudeuparius centromaculatus (Gyllenhal, 1833) [= P. pictus (Betta, 1857) syn. n.]; Pachytychius sparsutus (Olivier, 1807) [= P. aericollis (Betta, 1857) syn. n.]; Smicronyx coecus (Reich, 1797) [= S. minusculus (Betta, 1857) syn. n.]; Mecinus labilis (Herbst, 1795) [= M. vittatus (Betta, 1857) syn. n.]; Mecinus pascuorum (Gyllenhal, 1813) [= M. areolatus (Betta, 1857) syn. n.]; Mecinus latiusculus (Jacquelin du Val, 1855) [= M. flavipes (Betta, 1857) syn. n.]; Mecinus circulatus (Marsham, 1802) [= M. sericatus Betta, 1857 syn. n.].